GEOTHERMAL ESTIMATION BASED ON THE APPLICATION OF THE GRAVITY METHOD IN THE TANGKUBAN PARAHU MOUNTAIN AREA AND ITS SURROUNDINGS - Evita Helena, Lasma
The Tangkuban Parahu volcanic area is a geothermal prospect area in Bandung, West Java. Geothermal potential can be identified from the subsurface structure of the field. One of the geophysical methods that can be used in geothermal exploration is the gravity method. The ability of the gravity method to find values of rock density variations below the surface can be used to identify structures that control geothermal systems. The data obtained from the field is processed by making various corrections so that a complete Bouger anomaly value is obtained which shows the distribution of gravity anomaly values in the area, then modeling is carried out using the Talwani method to determine the subsurface conditions. From the results of the processing that has been done, the average density value of the study area is 2.4277 gr/cm3 . Based on data interpretation using 2D inversion modeling in the Tangkuban Parahu research area, several subsurface rock layers were obtained, namely sandstone layers, clay or claystone layers, and andesite rock layers. Areas with low gravity anomaly values which are indicated as potential sources of geothermal energy and are associated with the presence of geothermal manifestations around the study area.